The susceptibility of Trypanosoma congolense isolated in Zambézia Province (Mozambique) to isometamidium chloride, homidium chloride and diminazene aceturate - Penzhorn, Barend Louis (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2005.